2-Methylamino-5-nitrobenzoic acid - Raza, Abdul Rauf (International Union of Crystallography, 2010)
The title compound, C(8)H(8)N(2)O(4), is almost planar (r.m.s. deviation = 0.037 Å) and an intramolecular N—H⋯O hydrogen bond generates an S(6) ring. In the crystal, inversion dimers linked by pairs of O—H⋯O hydrogen bonds generate R (2) (2)(8) loops. Intermolecular N—H⋯O hydrogen bonds (involving the same H atom that forms the intramolecular hydrogen bond) link the dimers into infinite sheets lying parallel to (102).